Maternal Influences on Nausea and Vomiting in Early Pregnancy - Chan, Ronna L. (2011)
Symptoms of nausea and vomiting in early pregnancy (NVP) are common among pregnant women, but whether some women are more likely than others to experience these symptoms has not been well established. We examined potential risk factors for NVP symptom severity, timing of onset, and duration. We included 2,407 newly pregnant women who participated in a prospective cohort study on early pregnancy health between 2000 and 2004 in three U.S. cities. Data on NVP and other health information were collected through telephone interviews, early gestation ultrasound, and medical record abstractions. Generalized linear models were used to model possible risk factors for each NVP characteristic. Eighty-nine percent of women had NVP; for 99% of these, symptoms started in the first trimester. None of the characteristics examined were associated with having NVP. Among those with NVP, increasing risk of delayed symptoms onset was associated with advancing maternal age; increased risks were also seen among non-Hispanic Black [Risk ratio (RR) = 4.3, 95% confidence interval (CI): 1.6,11.6] and Hispanic women (RR = 2.3, 95% CI:0.4,11.5). NVP symptoms for multigravidae were more likely to last beyond the first trimester with each additional pregnancy. Most pregnant women experienced NVP. Nearly all of them, regardless of characteristics examined, had symptoms beginning in the first trimester. Maternal age, race/ethnicity, and gravidity were associated with delayed onset and symptoms that persisted into the second trimester.